Analisis Pengaruh Gaya Kepemimpinan, Motivasi Kerja, dan Displin Kerja Terhadap Kinerja Karyawan Pada PT ISS Indonesia - Noto Susanto (Peneliti.net, 2020)
The purpose of this study was to determine and conclusions about the influence of the three independent variables (leadership style, work motivation, and work discipline) on employee performance at PT. ISS Indonesia. The method used by the Associative method. The sample used was 150 respondents. Data analysis techniques with multiple linear regression analysis. The results of the study are as follows: There is a positive and significant influence of leadership style on employee performance at PT. ISS Indonesia. There is a positive and significant influence of work motivation on employee performance at PT. ISS Indonesia. There is a positive and significant effect of work discipline on employee performance at PT. ISS Indonesia. Simultaneously there is a positive and significant influence of leadership style, work motivation and work discipline on employee performance at PT. ISS Indonesia.